Analysis Of The Role Of Local Government In Resolving Agrarian Conflicts Based On Business Use Rights (HGU) (Case Study Of Pt Hevea Indonesia In Bogor District) - Silviana Tan (Semarang State University Undergraduate Law and Society Review, 2025)
Agrarian conflict is one that has occurred frequently since the New Order.  The existence of gaps or incompatibilities related to agrarian resources, particularly in gaps in tenure, perceptions, and concepts, as well as conflicting laws and policies, has been the main reason for agrarian conflict. One form of land tenure that is often a source of conflict is the Cultivation Rights Title (HGU). The role of local governments is very important in resolving HGU-based agrarian conflicts, especially in ensuring that land redistribution policies run well according to the principles of social justice. The research method used in this research is empirical juridical with a qualitative research approach and data collection techniques through interviews and documentation studies. The focus of the research lies on the role of local governments in resolving agrarian conflicts based on land use rights and the role of related institutions. That (1) The Regional Government has resolved the Agrarian Conflict of Land Use Rights (HGU) of PT Hevea Indonesia by forming the Agrarian Reform Task Force (GTRA) Team which assists the government in resolving land conflicts. (2) In resolving the HGU issue, BPN plays an active role in assisting the local government and BPN is the Chief Executive of GTRA.